A Study of List, Group, and Label Strategies on Vocabulary Acquisition in the Classroom - Najwa, Siti; Maximilian, Aksendro; Febriyanti, Febriyanti (STKIP PGRI Bandar Lampung, 2025)
This study investigated the impact of the List/Group/Label (LGL) method on vocabulary learning in eleventh-grade students at SMK Negeri 8 Bandar Lampung. The primary aim was to determine if a significant difference in academic performance existed between the experimental and control groups. The research population consisted of all eleventh-grade students in their second semester at SMK Negeri 8 Bandar Lampung, totaling 338 students spread across 10 classes. Two classes were selected as samples: XI MLPB 1 acted as the experimental group (36 students), while XI MPLB 2 served as the control group (35 students). This study employed a quantitative approach within a quasi-experimental design. Data gathering was carried out through vocabulary evaluations (pre-test and post-test). The results indicated a marked improvement in vocabulary learning for students in the experimental group taught using the LGL method in contrast to the control group. This suggests that the List/Group/Label method serves as an efficient strategy for enhancing students' vocabulary learning